Desain Off Street Parking Jangka Pendek dan Jangka Panjang Sebagai Solusi Permasalahan Lalu Lintas On Street Parking Pada Jalan Yos Sudarso, Kota Palangka Raya - , Viona Imanuella Dwi Putri; Murniati; Sutan Parasian Silitonga (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The Sangomang Culinary Area on Jalan Yos Sudarso, Palangka Raya City, is a popular destination whose operations take place at night. This popularity raises problems related to limited parking spaces, especially due to the high parking activity on the road (on street parking). This study aims to analyze the characteristics of existing parking, both on the road body and in the parking lot (off street parking), as well as design a new parking lot design that is able to accommodate a larger vehicle capacity. The methods used include the collection of primary data through field surveys related to volume, accumulation, duration, capacity, index, turnover rate, and parking space needs, as well as secondary data in the form of documentation of existing conditions. The results of the analysis show that the parking capacity in the courtyard is currently inadequate, with the highest parking volume reaching 278 vehicles on Saturday, consisting of 183 vehicles in on street parking and 95 vehicles in off street parking. Therefore, a new, more extensive and planned parking design is needed, as well as the calculation of estimated parking revenue using a fixed rate system based on the design.